Parents' Responses to Teacher Qualifications - Simon Chang; Deborah A. Cobb-Clark; Nicolás Salamanca (Institute of Labor Economics (IZA), 2020)
We identify the causal effect of teacher qualifications on parents' investments in their children. Exploiting a unique, high-stakes educational setting in which teachers are randomly assigned to classes, we show that parents react to more qualified teachers by increasing their financial investments in their children. The key mechanism is an increase in parents' belief that academic achievement is driven by student effort—for which financial investment is instrumental. However, higher teacher qualifications do not improve student test scores. This is likely due to a negative effect of teacher qualifications on students' belief in the importance of effort for academic achievement. Our findings uncover various family-wide behavioral reactions to teacher qualifications and highlight the intricacies in educational production within households.
Keywords: D10; I21; I24; 330; teacher quality; student achievement; parental investment; beliefs; school effort